Change in surgeon for revision rhinoplasty: The impact of patient demographics and surgical technique on patient retention. Issue 6 (12th November 2020) - Crawford, Kayva L.; Lee, Jason H.; Panuganti, Bharat A.; Burton, Brittany N.; Jafari, Aria; Hom, David B.; Watson, Deborah
Abstract: Objectives: A subset of patients who require revision rhinoplasty will change surgeons for their second procedure. We sought to investigate the rate of surgeon change and identify associated predictors using a population‐based, ambulatory surgery database. Methods/study design: In this retrospective review, 9172 rhinoplasty procedures over a 5‐year period were analyzed using the Healthcare Cost and Utilization Project (HCUP) Florida State Ambulatory Surgery and Services Database (SASD). We identified 380 patients who had at least two rhinoplasty procedures between 2009 and 2014. Logistic regression analysis was used to identify predictors of patients changing surgeons for their second documented rhinoplasty. Results: Among the 380/8531 (4.4%) patients who underwent a revision rhinoplasty, 117/380 (30.8%) patients changed surgeons for their subsequent procedure within a 5‐year period. Multivariable logistic regression identified a lower likelihood of surgeon change in patients undergoing functional or cosmetic cartilage grafting procedures (OR 0.342, 95%CI 0.155‐0.714, P = .006) and in patients who self‐paid for their procedure (OR 0.476, 95%CI 0.225‐0.984, P = .048). One hundred twenty‐four patients underwent a cosmetic revision rhinoplasty and were twice as likely to change surgeons as those who underwent functional revision rhinoplasty (OR 2.042 95%CI 1.046‐4.050, P = .038). Time elapsed (>2 years) was positively correlated with likelihood of surgeon change (OR 1.236, 95%CI 1.153‐1.333, P < .001). Conclusion: In our analysis, 30.8% of patients changed surgeons for their revision rhinoplasty. Cartilage grafting at the time of index procedure and cash payment correlated with a decreased likelihood of surgeon change. Patients were more likely to change surgeons with increased time elapsed or for an aesthetic revision. Clarifying features associated with surgeon change may help improve patient satisfaction and retention.